Multidrug resistance in Escherichia coli carrying integrons isolated from a pig farm with moderate antibiotic use - Torre, Eulalia de la (2015)
The emergence and dissemination of antimicrobial resistance in bacteria derived from food-producing animals is a consequence of intensive agricultural and veterinary use of antimicrobial compounds. The inappropriate use and prescribing of antibiotics, along with their use as growth promoters, is the main cause of the development of resistance. The potential risk of the transfer of this resistance through the food chain by bacteria such as Escherichia coli (E. coli), including food borne pathogens such as Shiga toxin-producing E. coli, implies a problem for public health (van den Bogaard and Stobberingh, 2000). Horizontal gene transfer is an important route of the dissemination. Integrons are genetic elements able to capture gene cassettes encoding antibiotic resistance from the environment and incorporate them by site-specific recombination. Integrons are gene-capture and expression systems characterized by the presence of an intI gene encoding an integrase, a recombination site (attI), and a promoter. The most frequently reported mobile integrons are class 1 and class 2 integrons, which have been shown to contribute to the spread of antimicrobial resistance genes. It is important to remark that the presence of integrase is potentially indicative of strains capable of recruiting antibiotic resistance genes (Cambray et al., 2010). Moreover, resistance genes and resistant bacteria in the environment are considered an ecological problem. Therefore, the investigation of commensal bacteria is important in order to assess the extent of the drug resistance problem. The aim of the present study was to evaluate the susceptibility to antibiotics in commensal integron-positive E. coli isolated from pigs from a pig farm in Argentina.